First Microbiological and Molecular Identification of Rhodococcus equi in Feces of Nondiarrheic Cats - De Paula, Carolina Lechinski [UNESP]; Silva, Rodrigo Otávio Silveira; Hernandes, Rodrigo Tavanelli [UNESP]; Júnior, Geraldo De Nardi; Babboni, Selene Daniela; Guerra, Simony Trevizan [UNESP]; Listoni, Fernando José Paganini [UNESP]; Giuffrida, Rogério; Takai, Shinji; Sasaki, Yukako; Ribeiro, Márcio Garcia [UNESP] (Hindawi, 2019)
Rhodococcus equi is responsible for infections in multiple-host animals. In humans, the prevalence of rhodococcus has increased worldwide and represents an emergent risk. R. equi is a soil-borne opportunistic bacterium isolated from feces of a wide variety of domestic species, except cats; thus, there is no known potential risk of its transmission from humans. Here, the mono- and cooccurrence of Rhodococcus equi and other bacteria and selected virulence markers were investigated in feces of nondiarrheic cats from urban (n=100) and rural (n=100) areas. Seven (7/200=3.5%) R. equi isolates were recovered in ceftazidime, novobiocin, and cycloheximide (CAZ-NB) selective media, exclusively of cats from three distinct farms (p=0.01), and these cats had a history of contact with horses and their environment (p=0.0002). None of the R. equi isolates harbored hosted-adapted plasmid types associated with virulence (pVAPA, pVAPB, and pVAPN). One hundred seventy-five E. coli isolates were identified, and 23 atypical enteropathogenic E. coli (aEPEC), 1 STEC (Shiga-toxin producing E. coli), and 1 EAEC (enteroaggregative E. coli) were detected. Eighty-six C. perfringens type A isolates were identified, and beta-2 and enterotoxin were detected in 21 and 1 isolates, respectively. Five C. difficile isolates were identified, one of which was toxigenic and ribotype 106. The main cooccurring isolates in cats from urban areas were E. coli and C. perfringens A (26/100=26%), E. coli and C. perfringens type A cpb2+ (8/100=8%), and aEPEC (eae+/escN+) and C. perfringens type A (5/100=5%). In cats from farms, the main cooccurring isolates were E. coli and C. perfringens type A (21/100=21%), E. coli and C. perfringens type A cpb2+ 8/100=8%), and E. coli and R. equi (4/100=4%). We identified, for the first time, R. equi in nondiarrheic cats, a finding that represents a public health issue because rhodococcus has been reported in both immunosuppressed and immunocompetent humans, particularly people living with HIV/AIDS.